A Unique Coupled Common Fixed Point Theorem for Symmetric (φ,ψ)-Contractive Mappings in Ordered G-Metric Spaces with Applications - Manish Jain; Kenan Taş (Journal of Applied Mathematics)
We establish the existence and uniqueness of coupled common fixed point for symmetric (φ,ψ)-contractive mappings in the framework of ordered G-metric spaces. Present work extends, generalize, and enrich the recent results of Choudhury and Maity (2011), Nashine (2012), and Mohiuddine and Alotaibi (2012), thereby, weakening the involved contractive conditions. Our theoretical results are accompanied by suitable examples and an application to integral equations.